Enhancing Evaluation Capacity to Advance Program Evaluation in Nursing Mentorship. - Kaminska, Karolina; Sousa, Sarah; Lawrence, Kimberly; DasGupta, Tracey; Skinner, Kelly (Nursing Leadership (1910-622X), 2025)
Building capacity within programs to conduct evaluation allows leaders to increase the potential of harnessing systematic assessment to improve program impact. At Sunnybrook Health Sciences Centre, Canada, nursing leaders leveraged evaluation capacity building (ECB) as a tool to improve the Transition Mentorship Program, an initiative using mentorship to support practice transitions and foster improved retention, a challenge in the nursing workforce, especially among newly registered nurses. In collaboration with evaluators at the University of Waterloo, Sunnybrook implemented an ECB intervention to bolster the program's evaluation capacity, bridge silos across clinical settings and embed standardized, evidence-informed processes. This case study describes this intervention while discussing lessons learned and recommendations for nurse leaders.